DC-DC converter with 50 kHz-500 kHz range of switching frequency for passive component volume reduction - Mohd Amirul Naim Kasiran; Asmarashid Ponniran; Nurul Nabilah Mad Siam; Mohd Hafizie Yatim; Nor Azmira Che Ibrahim; Asmawi Md Yunos (International Journal of Electrical and Computer Engineering (IJECE), 2021)
This paper presents the relationship of switching frequency towards passive components volume of DC-DC boost converter. Principally, the inductor current ripple and capacitor voltage ripple must be considered in order to design the inductor and capacitor, respectively. By increasing the switching frequency, smaller size and volume of passive component can be designed. As the consequences, the switching loss increases during switching transition at turn-ON and turn-OFF conditions. This paper used soft-switching technique to reduce the switching loss at turn-ON condition. The soft-switching technique is realized by adding resonant circuit in DC-DC boost converter. The effectiveness of resonant circuit will be analysed, thus, the efficiency of the converter can be improved. The range of switching frequency considered in the experimental are 50 kHz to 500 kHz. A 100 W prototype has been developed and tested in order to verify the principle. The switching loss experimentally confirm reduced by implementing soft-switching technique with efficiency converter improved from 96.36% to 97.12% when 500 kHz of switching frequency is considered. The passive components volume reduction is achieved when high switching frequency is used where the total volume of passive component when 50 kHz and 500 kHz are 0.083 dm3 and 0.010 dm3, respectively.